6.4x-7-2.9x=

Simple and best practice solution for 6.4x-7-2.9x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6.4x-7-2.9x= equation:


Simplifying
6.4x + -7 + -2.9x = 0

Reorder the terms:
-7 + 6.4x + -2.9x = 0

Combine like terms: 6.4x + -2.9x = 3.5x
-7 + 3.5x = 0

Solving
-7 + 3.5x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '7' to each side of the equation.
-7 + 7 + 3.5x = 0 + 7

Combine like terms: -7 + 7 = 0
0 + 3.5x = 0 + 7
3.5x = 0 + 7

Combine like terms: 0 + 7 = 7
3.5x = 7

Divide each side by '3.5'.
x = 2

Simplifying
x = 2

See similar equations:

| 4K-30=2(2k-16) | | 1(1-4)-2/4 | | 12xw=0.0144 | | -6x=-4-6 | | x-(x^2-x-6)=3 | | 7a+2c=330 | | 3/5c-7/2b | | 6(1+8x)=246 | | -7+10y=-14 | | (((x^1/2)*(y^-2))/((y)*(x^-7/4)))^4 | | 3x-3(4x+5x)=0 | | 2y/7-7/8=13/56 | | 3/4x1/2=-1/4x-1/4 | | 17=4-2n+5 | | -7v+5(1-6v)=301 | | X/4=-1.25 | | a=0.008(150) | | 1/3x-4=9/7-5/6x | | 3x-8x+66=2x+31 | | 6t^2+4=2t^2 | | ln(x)=3.29 | | 20x^2-82x+42=0 | | 2=y/2-3 | | (2x^6y^-5/5x^-4y^3)^-2 | | 45=60p | | 9m=-81 | | x-39/4=3/2 | | 4+1(1+3x)5= | | 4j-13j+10j=-17 | | -6m+2=3y-5 | | 5k-6+6k-22=3 | | 20x+4=8x+52 |

Equations solver categories